Biography of Heinz Oberhammer - Dakkouri, Marwan (2010)
Heinz Oberhammer was born on June 4th, 1939 in Innsbruck, Austria, where he attended school. After he graduated from high school in 1957 he studied physics and mathematics at the University of Innsbruck. He obtained his PhD in 1964 with a thesis on theoretical nuclear physics. Shortly after graduation he received an offer by a US government laboratory to continue working in the field of nuclear physics. The requirements for this job were an application for an immigration visa and commitment for at least 3 years. As everything was almost set and he was about to sign the contract, he received a notice from a friend that Prof. Simon Bauer at the Chemistry Department of the Cornell University was looking for a postdoc for doing electron diffraction. That was the first time Heinz had heard about electron diffraction. Luckily, he then applied for the post-doc position at Cornell since he wanted to go to an academic institution without commitment and restrictions. Thus, it was pure chance for him to get into electron diffraction.